One-dimensional warm electron transport in GaN quantum well wires at low temperatures - Sarkar, S.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
One-dimensional warm electron coefficient (β) and Ohmic mobility μ₀ in a square quantum well wire of GaN are studied for lattice temperatures in the range of 4-10 K, which are important from the application point of view. Electron scattering via deformation potential acoustic, piezoelectric, and ionized impurity are incorporated in the calculations. Carrier distribution is considered to be a heated Fermi-Dirac. Ohmic mobility (μ₀) is larger for a quantum well wires of greater width and decreases slowly with the rise of lattice temperature. β is negative, and its magnitude falls with increasing lattice temperature and is greater for wider width of the wire. The computed results are discussed in terms of the interplay of the various scattering mechanisms depending upon the model parameters.